ANÁLISE DA GEOMORFOLOGIA FLUVIAL DA BACIA DO RIO PREGUIÇAS: Padrões de drenagem na região dos Lençóis Maranhenses - JESUS, Veruska Costa de (2021)
In natural systems, river basins are the richest examples of the interaction of endogenous and exogenous forces acting on the earth's surface. In particular, there is the drainage network, which represents an indicator of changes that have occurred over time in the landscape of this hydrogeomorphological system. Within this perspective, this study aims to characterize and analyze the configuration of the fluvial morphological system of the Preguiças River basin (MA), which is located in the northeast region of Maranhão, aiming to propose the classification of the drainage pattern. The methodology involved the analysis of geology and the regional structural framework; the use of remote sensing images and geoprocessing techniques; the spatial characterization of the drainage network; the measurement of morphometric parameters; and sedimentological analysis. The results of these analyzes showed the heterogeneity of the drainage pattern in the upper, middle and lower reaches of the Preguiças river basin, where, for better characterization and classification of the drainage pattern, six homologous zones were defined. The classification resulted in: Zone I – 'wind disarranged' due to the greater interference of the wind input in the construction of this pattern; Zone II – 'interdune subparallel' due to the elongated and almost parallel character of the channels that flow into the interdune valley; Zone III – 'rectangular' due to the high structural influence evidenced by straight channels; Zone IV – 'semi-oriented subdendritic' due to low structural control with dendritic characteristics; Zone V – 'pinned lattice' due to the organizational aspect of the channels; and Zone VI – 'barbed' by evidence of tectonic reactivation through inverted channels. These classes were defined based on the way they are arranged in the landscape, on the lithological and structural aspects and on the processes that occur in the region. Some regional characteristics become the Preguiças River basin unique, including: the lithological and structural context, which is comprised of two distinct sedimentary basins; the presence of superficial deposits of unconsolidated wind input from the Pleistocene and Holocene; the climatic oscillations that occurred in the Quaternary, which allowed the development of relief forms that remain in the current landscape as inherited forms; the performance of continental and coastal processes; and finally, the flow of energy and matter interacting in opposite directions through the sedimentary cycle driven by fluvial action, which transports sediment in the SW-NE direction, and the sedimentary cycle driven by wind action, which transports sediment in the NE-SW direction. These characteristics contribute to the construction and evolution of different drainage patterns, which are controlled by lithostructural factors and by the processes responsible for the relief evolution.